MENCIPTAKAN VALUE BAGI KONSUMEN UNTUK MENDORONG IMPULS BUYING - HORAS, LAURA KATHIREN (Kajian Ilmiah Mahasiswa Manajemen, 2013)
This paper is to know whether impulse buying can give positive impacts to customers or not. Impulse buying is one way to buy a product without thinking too much but because of a TV, advertisements, famous brands. People think that doing that of buying is easier, efficient, practical and satistying. It will get more profits with low expenses charges. This marketing strategy has been coming since the last few years because it is able to attract customers to buy. The author is going to do some value to know the influences and the feedback of impulse buying. So consumers thinking about different ways to buy a goods at doing.